2018
DOI: 10.1158/2326-6066.cir-18-0098
|View full text |Cite
|
Sign up to set email alerts
|

FAP Delineates Heterogeneous and Functionally Divergent Stromal Cells in Immune-Excluded Breast Tumors

Abstract: Cancer-associated fibroblasts (CAFs) are generally associated with poor clinical outcome. CAFs support tumor growth in a variety of ways and can suppress antitumor immunity and response to immunotherapy. However, a precise understanding of CAF contributions to tumor growth and therapeutic response is lacking. Discrepancies in this field of study may stem from heterogeneity in composition and function of fibroblasts in the tumor microenvironment. Furthermore, it remains unclear whether CAFs directly interact wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
141
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 63 publications
8
141
0
Order By: Relevance
“…This was reflected in our data, in which expression of multiple pericyte markers was observed in the CAF3 population as well as in PDPN+ lymph node FRCs. A similar phenomenon was reported in a subcutaneous model of breast cancer, in which expression of pericyte markers was also observed in FRC populations 41 . Thus, the most robust method to differentiate between these cell types is to assess whether they are associated with endothelial vessels.…”
Section: Discussionsupporting
confidence: 81%
“…This was reflected in our data, in which expression of multiple pericyte markers was observed in the CAF3 population as well as in PDPN+ lymph node FRCs. A similar phenomenon was reported in a subcutaneous model of breast cancer, in which expression of pericyte markers was also observed in FRC populations 41 . Thus, the most robust method to differentiate between these cell types is to assess whether they are associated with endothelial vessels.…”
Section: Discussionsupporting
confidence: 81%
“…Since the initial report on different subpopulations of αSMA+ myofibroblasts in breast cancer (Lazard et al, 1993), it is now becoming clear that CAFs come with different flavours and that a heterogeneous population exists within a single breast tumour (Bartoschek et al, 2018;Busch et al, 2017;Calvo et al, 2013;Costa et al, 2018;Cremasco et al, 2018;Raz et al, 2018;Su et al, 2018). Here, we have presented data showing the existence of numerous CAF subpopulations in murine models of TNBC, expanding on previous findings within breast cancer that have proposed the existence of only 2 to 4 different CAF subpopulations (Bartoschek et al, 2018;Costa et al, 2018;Cremasco et al, 2018;Raz et al, 2018).…”
Section: Co-existence Of Numerous Caf Subpopulations In Breast Cancermentioning
confidence: 67%
“…Intra-tumoural heterogeneity of cancer cells in breast cancer is well recognised, and emerging evidence points toward breast cancer CAFs being equally heterogeneous (Bartoschek et al, 2018;Busch et al, 2017;Calvo et al, 2013;Costa et al, 2018;Cremasco et al, 2018;Raz et al, 2018;Su et al, 2018). While cancer cell heterogeneity is believed to arise through clonal evolution, the origins of CAFs, and how this influences the CAF heterogeneity, are still being intensely studied.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to malignant cells, the alteration of the stroma of solid tumors, namely the activation of cancer-associated fibroblasts has been described as critical determinant of cancer development and survival, and was also confirmed as therapeutic target [2]. It was shown that the expression of FAP prolyl endopeptidase, even on the cell surface or solubilized in the plasma, correlates with the malignancy and cisplatin resistance of carcinomas [29,[44][45][46]. Therefore, we have developed an assay to measure the activity of FAP cleaving the Fmoc-Gly-Pro-Cysteic acid-Ile-Gly-NH 2 peptide substrate ( Figure S2).…”
Section: Discussionmentioning
confidence: 97%